Cinta Pertama Adalah Luka: Studi Fenomenologis pada Perempuan Fatherless - Husna, Windi Asyriatul; Adri, Zakwan (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The fatherless phenomenon refers to the limited role of a father in a child's life, both physically and emotionally. This study aims to understand the experiences of emerging adult women who face fatherlessness, the dynamics involved, and the meaning they ascribe to the father's role. A qualitative phenomenological approach was employed, utilizing Interpretative Phenomenological Analysis (IPA). Interviews were conducted with two female participants, both aged 22. Findings indicate that participants perceive the father’s role in the family as strongly linked to communication, which serves as a key factor in fostering emotional closeness and psychological well-being. The main themes identified include the limitations of the father’s emotional role, social support, emotional reactions, and coping mechanisms. Participants developed various coping strategies, such as fostering independence, seeking father figures, or finding alternative social support systems. This study highlights that the experience of fatherlessness not only affects the relationship with the father but also influences self-concept formation, interpersonal relationship patterns, and expectations regarding future partners and family roles.